The Influence of the Openness of an E-Learning Situation on Adult Students’ Self-Regulation - Jézégou, Annie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
This article presents empirical research conducted with French speaking adults studying for a diploma. Their training took place mainly in e-learning. The goal of this research was to identify and explain the processes of influence existing between two specific dimensions: the degree of openness of the components of the e-learning situation and students’ self-regulated behaviors in the management of these components. This research was based on the socio-cognitive theory of self-regulation (Bandura, 1986; Schunk & Zimmerman, 2007; Zimmerman, 2002) and on a theoretical definition of the notion of “openness” (Jézégou, 2005). It applied the “actantial model” (Greimas, 1966; Hiernaux, 1977) for analyzing data collected while using a specific validated instrument of assessment of openness (Jézégou, 2010a). The main results of this empirical work are the role played by three psychological dimensions in the influence processes identified. More empirical study is required to confirm their validity.